Antilymphangiogenic therapy to promote transplant survival and to reduce cancer metastasis: What can we learn from the eye?. (February 2015) - Hos, Deniz; Schlereth, Simona L.; Bock, Felix; Heindl, Ludwig M.; Cursiefen, Claus
Abstract: The lymphatic vasculature is – amongst other tasks – essentially involved in inflammation, (auto)immunity, graft rejection and cancer metastasis. The eye is mainly devoid of lymphatic vessels except for its adnexa, the conjunctiva and the limbus. However, several pathologic conditions can result in the secondary ingrowth of lymphatic vessels into physiologically alymphatic parts of the eye such as the cornea or the inner eye. Therefore, the cornea has served as an excellent in vivo model system to study lymphangiogenesis, and findings from such studies have substantially contributed to the understanding of central principles of lymphangiogenesis also with relevance outside the eye. Grafting experiments at the cornea have been extensively used to analyze the role of lymphangiogenesis in transplant immunology. In this regard, we recently demonstrated the crucial role of lymphatic vessels in mediating corneal allograft rejection and could show that antilymphangiogenic therapy increases graft survival. In the field of cancer research, we recently detected tumor-associated lymphangiogenesis in the most common malignant tumors of the eye, such as conjunctival carcinoma and melanoma, and ciliochoroidal melanoma with extraocular extension. These neolymphatics correlate with an increased risk of local recurrence, metastasis and tumor related death, and may offer potential therapeutic targets for the treatment of these tumors. This review will focus on corneal and tumor-associated ocular lymphangiogenesis. First, we will describe common experimentally used corneal lymphangiogenesis models and will recapitulate recent findings regarding the involvement of lymphatic vessels in corneal diseases and transplant immunology. The second part of this article will summarize findings about the participation of tumor-associated lymphangiogenesis in ocular malignancies and their implications for the development of future therapeutic strategies.